Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/min8050206
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Di-(2-ethylhexyl) Phosphoric Acid (D2EHPA)-Tributyl Phosphate (TBP) Impregnated Resin and Application in Adsorption of Vanadium(IV)

Abstract: In order to improve the adsorption capability of solvent-impregnated resins (SIRs) for vanadium(IV) (V(IV)), the dual extractant (D2EHPA (Di-(2-ethylhexyl) phosphoric acid) and TBP (Tributyl phosphate)) impregnated resins (D-TIRs) were prepared by impregnating Amberlite TM XAD-16HP macroporous resins with the mixed extractant that is composed by different molar ratios of D2EHPA to TBP. The effects of the ratio of D2EHPA to TBP on the performance of D-TIRs were investigated. The results show that the impregnati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Figure 1 shows that the impregnation ratio of the N-TIRs significantly decline with the decrease of the molar ratio of N235 to TBP, which may be attributed to the different affinity of N235 and TBP for the support resins. As is known to us, the weak polar N235 have relatively higher affinity for the non-polar matrix of the resins matrix (Phenyl ethylene-divinyl benzene) in comparison to polar TBP [17]. As the molar ratio of N235 to TBP decreases, the content of N235 decreases and thus the impregnation ratio of the N-TIRs decline with the decreasing molar ratio.…”
Section: Effects Of the Used Mixturesmentioning
confidence: 89%
See 2 more Smart Citations
“…Figure 1 shows that the impregnation ratio of the N-TIRs significantly decline with the decrease of the molar ratio of N235 to TBP, which may be attributed to the different affinity of N235 and TBP for the support resins. As is known to us, the weak polar N235 have relatively higher affinity for the non-polar matrix of the resins matrix (Phenyl ethylene-divinyl benzene) in comparison to polar TBP [17]. As the molar ratio of N235 to TBP decreases, the content of N235 decreases and thus the impregnation ratio of the N-TIRs decline with the decreasing molar ratio.…”
Section: Effects Of the Used Mixturesmentioning
confidence: 89%
“…Figure 4 presents the FTIR spectra of the N-TIRs and NIRs. A literature shows that the characteristic vibration bands of P=O, 1281 cm −1 , would appear in the SIRs containing TBP [17]. It is obviously found that the characteristic adsorption peak of N235 (C-N bonds, 1099 cm −1 ) shifts to the lower wavenumber (1096 cm −1 ) and the intensity of the C-N bonds decreases (Figure 4a), and the P=O stretching bands also shifts to lower wavenumber 1263 cm −1 (Figure 4b), which may be attributed to that N235 is involved with TBP [23].…”
Section: Effects Of Impregnation Timementioning
confidence: 99%
See 1 more Smart Citation
“…The results show that the sole-TBP impregnated resins have no adsorption capability for V(IV), indicating that the adsorption of V(IV) is attributed to HDEHP. 75…”
Section: Tributyl Phosphate (Tbp)mentioning
confidence: 99%
“…Many projects are planning to follow the SX path and are considering including up to three or four SX plants in series, with each of them using a different reagent. Ketoximes and aldoximes based extractants such as LIX 984N and MEXTRAL 984N are a judicious choice for removal of copper while D2EHPA is mainly used for the purification of cobalt sulphate solutions in order to remove iron, zinc and manganese (Roux et al, 2007;Kopper Chemical Industry, 2019a;Sato et al, 1985;Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%